Analisis Kriminologi Terhadap Residivis Anak Sebagai Pelaku Tindak Pidana Kekerasan Seksual - Akbar Anugrah Fantono (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The aim of this research is to analyze the factors that cause recidivism committed by children as perpetrators of criminal acts of sexual violence, and to analyze efforts to prevent the repetition of criminal acts committed by children as perpetrators of criminal acts of sexual violence. The research results show that the factors that influence the recidivism of children as perpetrators of criminal sexual abuse are family factors, economic factors, socio-cultural environmental factors, and technological factors. Efforts made by legal authorities to overcome the occurrence of recidivism committed by children as perpetrators of criminal acts of sexual violence are carried out through various efforts including preventive and repressive efforts.